Endoscopic papillary balloon intermittent dilatation and endoscopic sphincterotomy for bile duct stones - Fu, Bai-Qing (Baishideng Publishing Group Co., Limited, 2013)
AIM: To compare the effectiveness and safety of endoscopic papillary balloon intermittent dilatation (EPBID) and endoscopic sphincterotomy (EST) in the treatment of common bile duct stones. METHODS: From March 2011 to May 2012, endoscopic retrograde cholangiopancreatography was performed in 560 patients, 262 with common bile duct stones. A total of 206 patients with common bile duct stones were enrolled in the study and randomized to receive either EPBID with a 10-12 mm dilated balloon or EST (103 patients in each group). For both groups a conventional reticular basket or balloon was used to remove the stones. After the procedure, routine endoscopic nasobiliary drainage was performed. RESULTS: First-time stone removal was successfully performed in 94 patients in the EPBID group (91.3%) and 75 patients in the EST group (72.8%). There was no statistically significant difference in terms of operation time between the two groups. The overall incidence of early complications in the EPBID and EST groups was 2.9% and 13.6%, respectively, with no deaths reported during the course of the study and follow-up. Multiple regression analysis showed that the success rate of stone removal was associated with stone removal method [odds ratio (OR): 5.35; 95%CI: 2.24-12.77; P = 0.00], the transverse diameter of the stone (OR: 2.63; 95%CI: 1.19-5.80; P = 0.02) and the presence or absence of diverticulum (OR: 2.35; 95%CI: 1.03-5.37; P = 0.04). Postoperative pancreatitis was associated with the EST method of stone removal (OR: 5.00; 95%CI: 1.23-20.28; P = 0.02) and whether or not pancreatography was performed (OR: 0.10; 95%CI: 0.03-0.35; P = 0.00). CONCLUSION: The EPBID group had a higher success rate of stone removal with a lower incidence of pancreatitis compared with the EST group.